Phytoremediation of Heavy Metal Contaminated Soil by Using Some Ornamental Plants - Adepoju, Adedoyin Damilola; Adejuyigbe, Christopher Olu; Olosunde, Olatunde Musibau; Ajiboye, Godwin Anjorin (Agro Bali : Agricultural Journal, 2024)
This study aims to assess the effectiveness of two different varieties of ornamental plants in remediating soil contaminated with cadmium and lead. The study was a two-cycle pot experiment with three replications arranged in a completely randomized design. The treatments include ornamental plants and contamination levels. Ornamental plants include Solenostemon scutellarioides (L.) Codd. var. Religious radish and Red-trailing-queen; Codiaeum variegatum L. var. Gold dust and Oakleaf. The concentrations were P0 (Pb at 0 mg.kg-1, Cd at 0 mg.kg-1), P1 (Pb at 1000 mg.kg-1, Cd at 2 mg.kg-1), P2 (Pb at 1500 mg.kg-1, Cd at 5 mg.kg-1), and P3 (Pb at 2000 mg.kg-1, Cd at 10 mg.kg-1). Dry matter weight (DMW), bioconcentration factor (BCF), and translocation factor (TF) were determined after harvest. The results showed that all plants’ DMW of shoot > DMW of root. Codiaeum variegatum varieties had BCF and TF of Cd higher than that of S. scutellarioides varieties. Similarly, S. scutellarioides varieties showed higher BCF and TF of Pb; however, there is a limit to how much Pb S. scutellarioides varieties may absorb from the soil, as BCF of Pb decreased after 1500 mg.kg‑1 lead contamination. The study found that the ornamental plants had high TF and low BCF values at high cadmium and lead levels, indicating their role as phytostabilizers. Among the plants studied, Oakleaf was identified as the most efficient phytostabilizer for cadmium, while Religious radish proved to be the most effective for lead.